Taxonomic studies of the genus Phymaturus (IGUANIA: LIOLAEMIDAE): Description of four new species. - Lobo Gaviola, Fernando Jose (2010)
After the study of a diverse collection of Phymaturus from three Argentinian institutions and additional samples collected in the last two years we discovered several populations of uncertain taxonomic status. Based on 93 morphological characters of squamation, color pattern, gular and nuchal folds, precloacal pores, and morphometric data, we conclude that at least four of those are independent lineages which require formal description. Characters related to sexual dimorphism and dichromatism as well as the ontogenetic change of several others, from juvenile to adult specimens, are described. According to the most recent revision of the genus (Lobo and Quinteros, 2005a) and considering the descriptions made in the last four years, the taxonomic composition of the genus was raised to 23 species. In this study we provide the formal description of four additional new taxa, including their diagnosis and detailed comparisons with other members of their species groups. Two new species belong to the patagonicus group (provinces of Chubut and Rio Negro, in Patagonia between 46° and 41° of latitude) while the other two belong to the palluma group (Neuquén and Catamarca provinces, western Argentina, 39° and 27‑26°30’of latitude respectively). With the exception of one case for which four localities are reported, all new species are restricted to their type localities. This fact confirms a common historical distributional pattern for most species of the genusPhymaturus from three Argentinian institutions and additional samples collected in the last two years we discovered several populations of uncertain taxonomic status. Based on 93 morphological characters of squamation, color pattern, gular and nuchal folds, precloacal pores, and morphometric data, we conclude that at least four of those are independent lineages which require formal description. Characters related to sexual dimorphism and dichromatism as well as the ontogenetic change of several others, from juvenile to adult specimens, are described. According to the most recent revision of the genus (Lobo and Quinteros, 2005a) and considering the descriptions made in the last four years, the taxonomic composition of the genus was raised to 23 species. In this study we provide the formal description of four additional new taxa, including their diagnosis and detailed comparisons with other members of their species groups. Two new species belong to the patagonicus group (provinces of Chubut and Rio Negro, in Patagonia between 46° and 41° of latitude) while the other two belong to the palluma group (Neuquén and Catamarca provinces, western Argentina, 39° and 27‑26°30’of latitude respectively). With the exception of one case for which four localities are reported, all new species are restricted to their type localities. This fact confirms a common historical distributional pattern for most species of the genuspatagonicus group (provinces of Chubut and Rio Negro, in Patagonia between 46° and 41° of latitude) while the other two belong to the palluma group (Neuquén and Catamarca provinces, western Argentina, 39° and 27‑26°30’of latitude respectively). With the exception of one case for which four localities are reported, all new species are restricted to their type localities. This fact confirms a common historical distributional pattern for most species of the genuspalluma group (Neuquén and Catamarca provinces, western Argentina, 39° and 27‑26°30’of latitude respectively). With the exception of one case for which four localities are reported, all new species are restricted to their type localities. This fact confirms a common historical distributional pattern for most species of the genus.